(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Aim: This research focuses on minimizing the Tool Wear (TW) by comparing the performance of conventional uncoated HSS drill bit with TiCN drill bit for the machining of LDX 2205 duplex stainless steel in novel CNC drilling machine. Materials and Methods: The materials used for drill bits were Titanium Carbonitride (TiCN) coated HSS drill bit and uncoated HSS drill bit. LDX 2205 Duplex Stainless Steel was used as workpiece. A total of 40 specimens were divided into 2 groups with 80% G-Power calculator, to measure the TW of two drill bits in novel CNC drilling machine. Cutting force, drill depth, spindle speed, tool geometry, rate of feed were the controlled factors. Results: Observed results for each drill bit were recorded and analyzed using SPSS Software. Final experimental values of TW were investigated and obtained, having mean TW value of 0.9324 mm for the HSS drill bit and mean TW value of 0.7502 mm for TiCN drill bit. These values were obtained with a significance level of 0.030 which is less than 0.05 (p<0.05). Conclusion: Within the limits of this study, TiCN drill bit has lower tool wear when compared to the HSS drill bit in the novel CNC drilling of LDX 2205 duplex stainless steel.